2022
DOI: 10.3390/healthcare10060979
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Burnout Syndrome among Physicians during the Outbreak of COVID-19 Pandemic—A Systematic Literature Review

Abstract: Background: Studies in the recent decades show that the medical profession has a high risk to develop burnout due to constant exposure to mental and physical suffering or death. The pandemic period induced additional stress for healthcare professionals due to the likelihood of a high rate of infection, long working shifts, using protective equipment, staying away from family, implementing new medical procedures. The present study is focusing on assessing the prevalence of burnout among physicians working in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 75 publications
3
37
1
2
Order By: Relevance
“…Known-groups method identified that females, participants with a chronic condition, and those with worse health status experienced higher levels of burnout. Several systematic reviews confirm that female gender is associated with high prevalence of burnout among healthcare workers during the pandemic (Claponea et al, 2022; Lluch et al, 2022; Shaikh et al, 2022). Moreover, several studies during the pandemic confirmed that poor physical/mental health was a predictor for increased healthcare workers’ burnout (Arrogante & Aparicio-Zaldivar, 2020; Kim et al, 2022; La Torre et al, 2021; Malagón-Aguilera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Known-groups method identified that females, participants with a chronic condition, and those with worse health status experienced higher levels of burnout. Several systematic reviews confirm that female gender is associated with high prevalence of burnout among healthcare workers during the pandemic (Claponea et al, 2022; Lluch et al, 2022; Shaikh et al, 2022). Moreover, several studies during the pandemic confirmed that poor physical/mental health was a predictor for increased healthcare workers’ burnout (Arrogante & Aparicio-Zaldivar, 2020; Kim et al, 2022; La Torre et al, 2021; Malagón-Aguilera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the use of music as a means for coping with highly emotional situations during the pandemic is noted (and this is an original finding, not investigated in similar studies). Experiencing burnout is widespread among medical professionals and has been estimated at between 14.7% and 90.4% in recent years [ 47 ]. Our sample is no exception, but it presents some peculiarities: compared to other Italian studies (7, 9), emotional exhaustion is in line with the findings in the literature, while depersonalisation and personal accomplishment appear much higher.…”
Section: Discussionmentioning
confidence: 99%
“…The Coronavirus Disease 2019 (COVID- 19) is an acute respiratory illness that spreads through respiratory droplets and close contacts [1][2][3]. Almost in all world regions, COVID-19 necessitated wearing facemasks to the general population, at least between 2020 and 2022 [1,4].…”
Section: Introductionmentioning
confidence: 99%